Volume 3: Coal, Biomass, and Alternative Fuels; Cycle Innovations; Electric Power; Industrial and Cogeneration; Organic Rankine 2018
DOI: 10.1115/gt2018-77274
|View full text |Cite
|
Sign up to set email alerts
|

Technology Application to MHPS Large Flame F Series Gas Turbine

Abstract: The development of gas turbines, Mitsubishi Hitachi Power Systems, Ltd. (MHPS) has continued to pursue and contribute to society in terms of global environmental conservation and stable energy supply. MHPS leverages its abundant gas turbine operation experience and takes advantage of its extensive advanced technologies research on the Japanese National Project. MHPS has been participating in this project since 2004. Recent years’ achievements include the demonstration of a gas turbine combined c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Advanced gas turbine can be described as upgrading the standard gas turbine to improve its reliability in terms of prolonging design life, efficiency in terms of improved power output, and durability in terms of enhanced operational flexibility [14][15][16]. The upgraded works include the use of upgraded superalloys, improved cooling holes configuration in both external film cooling and internal cooling, the application of TBC, and the use of an upgraded combustion system.…”
Section: Advanced Gas Turbinesmentioning
confidence: 99%
See 1 more Smart Citation
“…Advanced gas turbine can be described as upgrading the standard gas turbine to improve its reliability in terms of prolonging design life, efficiency in terms of improved power output, and durability in terms of enhanced operational flexibility [14][15][16]. The upgraded works include the use of upgraded superalloys, improved cooling holes configuration in both external film cooling and internal cooling, the application of TBC, and the use of an upgraded combustion system.…”
Section: Advanced Gas Turbinesmentioning
confidence: 99%
“…The differences in temperature reduction by different TBC thicknesses and number of cooling holes have also been elaborated in the study, and the summary is shown in Figure 7. Fujimoto et al have discussed the upgrading works that have been conducted to optimize the hybrid TBC-assisted cooling air by increasing the TBC thickness and modifying the shape of the cooling hole [16]. Taniguchi et al in their work modified the turbine blade cooling holes to improve the cooling performance [31].…”
Section: Tbc-assisted Cooling Air In Advanced Gas Turbinementioning
confidence: 99%